Combination PT-PCR with in vitro Transcription-Translation System: Rapid and Simple Approach for Monoclonal Antibody Production - Ali, Muhamad (Indonesian Journal of Biotechnology, 2009)
We have developed a simple and efficient system for screening and generation of monoclonal antibodies, which can bypass conventional monoclonal antibody production system that includes time-consuming, labor-intensive establishment and cultivation. Our method consist of: (1) cDNA synthesis from single B cells of immunized mouse, followed by (ii) PCR amplification of the Lc and Hc (Fd portion) cDNAs separately using low concentration (0,05 ìM) of the respective cDNA-specific primers with 5’ homotags in the presence of the homotag-specific primer (0,5 ìM), (iii) overlapping PCR of the amplified Lc and Hc cDNAs with the cassettes for the T7 promoter (T7P) and T7 terminator (T7T) to construct the following expression units: T7P-Lc-T7T and T7P-Hc-T7T, and (iv) in vitro expression of these units using an Escherichia coli S30 extract followed by ELISA screening without purification. Light-and heavy-chain cDNA were amplified and expressed using in vitro system, thus avoiding time consuming steps of cloning and bacterial expression. Having successfully amplified and expressed Lc and Hc genes from single B cells in rapid, simple, versatile, labor-saving, and cost effective, this method seem to be useful and applicable for the high-throughput monoclonal antibody generation.